Faktor-Faktor Yang Berhubungan Dengan Perilaku Merokok Di Lingkungan Kerja Pada Pegawai Laki-Laki Di Bidokkes Polda Bengkulu - Effendi, Santoso Ujang; Apriantri, Rina; Wullandary, Sekar Ayu; Suryani (Jurnal Vokasi Kesehatan, 2024)
The World Health Organization (WHO) states that Indonesia is in 3rd place after China and India as the country with the largest number of smokers in the world. This research aims to look at the factors related to smoking behavior in the work environment among male employees at the Bengkulu Regional Police's Bidokkes. This research used a cross-sectional design, a total sampling technique, namely all permanent employees and male honorary employees of the Bengkulu Police Department, both smokers and non-smokers, totaling 50 people. The results of the univariate research showed that there were 25 people (50.0%) with good knowledge, there were 23 people (46.0%) with poor psychology, 29 people (58.0%) who had an unsupportive attitude, there were 34 people (68, 0%) who smoke. Bivariate analysis results show a relationship between knowledge with a value of p = 0.001, psychology with a value of p = 0.003 and attitude with a value of p = 0.001 with smoking behavior in the work environment among male employees at the Bengkulu Regional Police Bidokkes with a medium relationship category. It is recommended that Bidokkes provide a smoking-free area and create clear standard operating procedures regarding employees who smoke, so that no employees smoke in the Bengkulu Biddokes environment.